Extracellular acidosis and very low [Na+] inhibit NBCn1‐ and NHE1‐mediated net acid extrusion from mouse vascular smooth muscle cells. (25th April 2017) - Bonde, L.; Boedtkjer, E.
Abstract: Aim: The electroneutral Na +, HCO 3 − cotransporter NBCn1 and Na + /H + exchanger NHE1 regulate acid–base balance in vascular smooth muscle cells (VSMCs) and modify artery function and structure. Pathological conditions – notably ischaemia – can dramatically perturb intracellular (i) and extracellular (o) pH and [Na + ]. We examined effects of low [Na + ]o and pHo on NBCn1 and NHE1 activity in VSMCs of small arteries. Methods: We measured pHi by 2′, 7′‐bis‐(2‐carboxyethyl)‐5‐(and‐6)‐carboxyfluorescein‐based fluorescence microscopy of mouse mesenteric arteries and induced intracellular acidification by NH 4 + prepulse technique. Results: NBCn1 activity – defined as Na + ‐dependent, amiloride‐insensitive net base uptake with CO2 / HCO 3 − present – was inhibited equally when pHo decreased from 7.4 (22 mm HCO 3 − /5% CO2 ) by metabolic (pHo 7.1/11 mm HCO 3 − : 22 ± 8%; pHo 6.8/5.5 mm HCO 3 − : 61 ± 7%) or respiratory (pHo 7.1/10% CO2 : 35 ± 11%; pHo 6.8/20% CO2 : 56 ± 7%) acidosis. Extracellular acidosis more prominently inhibited NHE1 activity – defined as Na + ‐dependent net acid extrusion without CO2 / HCO 3 − present – at both pHo 7.1 (45 ± 9%) and 6.8 (85 ± 5%). Independently of pHo, lowering [Na + ]o from 140 to 70 mm reduced NBCn1 and NHE1 activity <20% whereas transport activities declined markedly (25–50%) when [Na + ]o was reduced to 35 mm . Steady‐state pHi decreased more during respiratory (ΔpHi /ΔpHo  = 71 ± 4%) than metabolic (ΔpHi /ΔpHo  = 30 ± 7%) acidosis. Conclusion: Extracellular acidification inhibits NBCn1 and NHE1 activity in VSMCs. NBCn1 is equivalently inhibited when pCO2 is raised or [ HCO 3 − ]o decreased. Lowering [Na + ]o inhibits NBCn1 and NHE1 markedly only below the typical physiological and pathophysiological range. We propose that inhibition of Na + ‐dependent net acid extrusion at low pHo protects against cellular Na + overload at the cost of intracellular acidification.